2017
DOI: 10.1155/2017/5052870
|View full text |Cite
|
Sign up to set email alerts
|

Antcin‐H Isolated from Antrodia cinnamomea Inhibits Renal Cancer Cell Invasion Partly through Inactivation of FAK‐ERK‐C/EBP‐β/c‐Fos‐MMP‐7 Pathways

Abstract: Antcin-H, a natural triterpene, is purified from a famous anticancer medicinal mushroom, Antrodia cinnamomea, in Taiwan. This study showed that antcin-H inhibited the growth of human renal carcinoma 786-0 cells; the IC50 value (for 48 h) was 170 μM. Besides, the migration and invasion of 786-0 cells were suppressed by antcin-H under noncytotoxic concentrations (<100 μM); these events were accompanied by inhibition of FAK and Src kinase activities, decrease of paxillin phosphorylation, impairment of lamellipodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…In addition, a previous study has shown that antcin-K, isolated from the fruiting bodies of basswood-cultivated A. cinnamomea, inhibits human hepatoma cell metastasis via suppression of integrin-mediated adhesion, migration, and invasion [34]. Another study demonstrated that antcin-H from cultivated fruiting bodies of A. cinnamomea inhibits renal cancer cell invasion through inactivation of the FAK-ERK-C/EBP-β/ c-Fos-MMP-7 pathways [31]. In the present study, we found that ATA inhibits metastasis of HBCCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a previous study has shown that antcin-K, isolated from the fruiting bodies of basswood-cultivated A. cinnamomea, inhibits human hepatoma cell metastasis via suppression of integrin-mediated adhesion, migration, and invasion [34]. Another study demonstrated that antcin-H from cultivated fruiting bodies of A. cinnamomea inhibits renal cancer cell invasion through inactivation of the FAK-ERK-C/EBP-β/ c-Fos-MMP-7 pathways [31]. In the present study, we found that ATA inhibits metastasis of HBCCs.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-cancer properties of A. cinnamomea have been attributed to its unique composition of phytochemicals such as antroquinonols, antcins, and antrodins [12-15, 23, 24]. Among them, the antcins (ATA, antcin-B, antcin-C, antcin-D, antcin-E, antcin-F, antcin-G, antcin-H, antcin-I, antcin-K, and antcin M) are steroid-like compounds that exert various biological activities including, anti-inflammation [16,25], hepatoprotection [26][27][28], anti-aging [29], anti-cancer [30][31][32][33], and anti-metastasis [34]. We have previously reported that ATA isolated from the fruiting bodies of A. cinnamomea inhibits inflammation in lung cells via mimicking a glucocorticoid receptor agonist, and this effect was highly comparable with synthetic steroids, such as cortisone and dexamethasone [16].…”
Section: Discussionmentioning
confidence: 99%
“…For example, YMGKI-1, purified from natural products of Antrodia cinnamomea, was shown to effectively decrease cell viability of HNSCC cells and successfully inhibit tumorigenicity of SAS (14). Antcin-H, a type of triterpene isolated from Antrodia cinnamomea, was reported to inhibit proliferation and migration of human renal carcinoma 786-O cells by targeting MMPs and TIMPs (10). Furthermore, recent articles (12,13,16) revealed that EEA enhances chemosensitivity of several carcinomas, indicating that EEA can be used as adjuvant treatment combined with conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established its anti-tumor effects (1,8,9). The protective role of the ethanol extract of fruiting bodies of Antrodia cinnamomea has been experimentally demonstrated in several malignancies including renal cancer (10), lung cancer (7,11), hepatocellular carcinoma (12), and breast cancer (13), while the effects on head and neck cancer were seldom evaluated (14). Several active components isolated from raw extracts of Antrodia cinnamomea, mainly including triterpenoids, dicarboxylic acids, and polysaccharides (15), have been identified and can effectively inhibit proliferation, invasion, and migration of tumor cells (10,14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation